Screening and characterisation of endogenous betaretrovirus in small mammals / Nur Fatin Aman Mohd Razlan Mahandran - Mohd Razlan Mahandran, Nur Fatin Aman (2017)
Betaretrovirus is capable of crossing the barrier between human and other animals through cross-species transmission. Bats and guinea pigs have a great potential as a vector for virus infections a:s they possess ecological traits that enable them to spread viral diseases geographically. An investigation was carried out using bioinformatic and molecular approaches to search for the presence of endogenous betaretrovirus in bats (PvEB) and guinea pigs (CpEB) genome. A total of 60 genome project databases were screened using BLAST and 46 tissue samples from small mammals were screened for pro;.rt gene using PCR amplification. Only 2 species were further investigated due to their significant BLAST result, namely flying (ox (Pteropus vampyrus) and guinea pig ( Cavia porcellus). Based on insilico characterisation work, a full-length genome of PvEB and CpEB was found with the size of 8772bp and. 8543bp respectively. Both had a typical genomic organisation of a betaretrovirus. Conserved motifs of gag,pol and env were further supported through Pfam-A analysis and protein structure prediction. Subsequently, phylogenetic tree analysis of gag, pol and full-length sequence had placed PvEB and CpEB robustly within betaretroviruses clade with strong .bootstrap support. Age estimation has revealed that each PvEB and CpEB had diverged from its host 8.8 and 47.lmya respectively. The results of bioinformatic findings were further verified through PCR amplification of pro-rt region in PvEB and CpEB.. Therefore, based on bioinformatics and molecular approaches, it is evident that PvEB and CpEB have significant characteristics of a type'."D betaretrovirus and have involved in cross-species transmission.